3,3-Bis(2-hydroxyethyl)-1-[(4-methylphenyl)carbonyl]thiourea: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Ainnul H. S. Azizan, *; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
In the title tri-substituted thiourea derivative, C13H18N2O3S, the thione-S and carbonyl-O atoms lie, to a ﬁrst approximation, to the same side of the molecule [the S—C—N—C torsion angle is-49.3 (2)⁰]. The CN2S plane is almost planar (r.m.s. deviation = 0.018 A ˚ ) with the hydroxyethyl groups lying to either side of this plane. One hydroxyethyl group is orientated towards the thioamide functionality enabling the formation of an intramolecular N—H...O hydrogen bond leading to an S(7) loop. The dihedral angle [72.12 (9)⁰] between the planes through the CN2S atoms and the 4-tolyl ring indicates the molecule is twisted. The experimental molecular structure is close to the gas-phase, geometryoptimized structure calculated by DFT methods. In the molecular packing, hydroxyl-O—H...O(hydroxyl) and hydroxyl-O—H...S(thione) hydrogen bonds lead to the formation of a supramolecular layer in the ab plane; no directional interactions are found between layers. The inﬂuence of the speciﬁed supramolecular interactions is apparent in the calculated Hirshfeld surfaces and these are shown to be attractive in non-covalent interaction plots; the interaction energies point to the important stabilization provided by directional O—H...O hydrogen bonds.